Perencanaan Keuangan Pribadi Mahasiswa dengan Model Time Value of Money - Aulia Aulia Eka Fatmawati; Fajar Fajar Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Personal financial planning is a crucial aspect that must be well-managed by students to effectively achieve both short-term and long-term financial goals. This study aims to analyze students' personal financial planning using the Time Value of Money (TVM) model through a quantitative approach. The TVM model was chosen for its ability to calculate the value of money at different points in time, enabling students to make rational financial decisions based on future monetary projections. The research employed a primary data collection method through questionnaires distributed to active students across various faculties. The collected data were analyzed using descriptive and inferential statistical techniques to assess students' understanding of the TVM concept and its application in personal financial planning. The results indicate a significant positive correlation between knowledge of TVM and students' ability to develop optimal financial plans. This study provides practical insights to help students manage their finances by considering both time and risk factors, thereby enhancing financial literacy and fostering financial independence. The findings also have implications for the development of campus-based financial education programs.